2016
DOI: 10.1016/j.neuron.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Neural Architecture of Hunger-Dependent Multisensory Decision Making in C. elegans

Abstract: SUMMARY Little is known about how animals integrate multiple sensory inputs in natural environments to balance avoidance of danger with approach to things of value. Furthermore, the mechanistic link between internal physiological state and threat-reward decision making remains poorly understood. Here we confronted C. elegans worms with the decision whether to cross a hyperosmotic barrier presenting the threat of desiccation to reach a source of food odor. We identified a specific interneuron that controls this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(152 citation statements)
references
References 54 publications
4
147
1
Order By: Relevance
“…Several computational models have been constructed to elucidate behavioral mechanisms underlying C. elegans taxis behavior (26)(27)(28). These models have been built using detailed observation of animals moving in gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Several computational models have been constructed to elucidate behavioral mechanisms underlying C. elegans taxis behavior (26)(27)(28). These models have been built using detailed observation of animals moving in gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral paradigms used to investigate multisensory integration in C. elegans have been developed by taking advantage of the sensitivity of the worms to an array of sensory modalities. These paradigms include: 1) Expose the worms to two sensory cues of opposing valence and ask the animals to make a decision between the cues [22,23]; 2) Expose the worms to a single sensory stimulus that is paired with a contextual cue, such as ambient temperature or food availability [2427]. Using these paradigms, it has been shown that integrated behavioral responses are regulated by several distinct, but overlapping neuronal and circuit mechanisms, which we will review as the following.…”
Section: Elegans Performs Multisensory Integrationmentioning
confidence: 99%
“…This high degree of convergence provides an anatomical basis for these interneurons to act as coincidence detectors to receive and process inputs from multiple sensory neurons that respond to simultaneously presented sensory cues of different modalities [22,23,48,6265]. For example, when worms are simultaneously confronted with an attractive odorant diacetyl sensed by the chemosensory neurons AWA and an aversive stimulant Cu 2+ sensed by the polymodal sensory neurons ASH, they make a behavioral decision between approach and avoidance.…”
Section: Cellular and Circuit Mechanisms Underlying Multisensory Intementioning
confidence: 99%
See 2 more Smart Citations